Red algae industrial residues as a sustainable carbon platform for the co-production of poly-3-hydroxybutyrate and gluconic acid by Halomonas boliviensis - Bondar, Maryna; Pedro, Filipa; Oliveira, M. Conceição; da Fonseca, M. Manuela R.; Cesário, M. Teresa (Frontiers in Bioengineering and Biotechnology, 2022)
Polyhydroxyalkanotes (PHAs) production using halophilic bacteria has been revisited because less severe operational conditions with respect to sterility can be applied, alleviating also production costs. Halomonas boliviensis was selected because it is a moderate halophile able to grow and attain high poly-3-hydroxybutyrate (P3HB) contents under 5-45 g/L NaCl concentrations, conditions that discourage microbial contamination. Industrial residues of the red alga Gelidium corneum after agar extraction were used as sugar platforms to reduce costs associated with the carbon-source. These residues still comprise a high carbohydrate content (30-40% w/w) of mainly cellulose, and their hydrolysates can be used as substrates for the bioproduction of value-added products. Preliminary assays using glucose were carried out to determine the best conditions for growth and P3HB production by H. boliviensis in bioreactor fed-batch cultivations. Two strategies were addressed, namely nitrogen or phosphorus limitation, to promote polymer accumulation. Similar P3HB cell contents of 50 % (gpolymer/gCDW) and yields YP3HB/glucose of 0.11-0.15 g polymer/g glucose were attained under both conditions. However, higher specific productivities were reached under P-limitation and thus this strategy was adopted in the subsequent work. Two organic acids, resulting from glucose metabolism were identified to be gluconic and 2-oxoglutaric acid. Reducing the oxygen concentration in the cultivation medium to 5 % sat was found to minimize organic acid production and enhance Operating conditions to minimize organic acid production and enhance the yield of polymer on sugar (YP3HB/glucose) to 0.20 gP3HB/.g-1glucose. Finally, fed-batch cultivations using G. corneum hydrolysates as the only C-source, achieved an overall volumetric productivity of 0.47 g/(L.h), 40 % polymer accumulation and negligible gluconic acid production.